Death by a thousand cuts : the fight over taxing inherited wealth - Graetz, Michael J. (Princeton University Press, 2006)
This fast-paced book by Yale professors Michael Graetz and Ian Shapiro unravels the following mystery: How is it that the estate tax, which has been on the books continuously since 1916 and is paid by only the wealthiest two percent of Americans, was repealed in 2001 with broad bipartisan support? The mystery is all the more striking because the repeal was not done in the dead of night, like a congressional pay raise. It came at the end of a multiyear populist campaign launched by a few individuals, and was heralded by its supporters as a signal achievement for Americans who are committed to t.